Pengaruh pesan instagram @Ricmaupdate terhadap minat remaja untuk menjadi anggota remaja islam masjid cut meutia (Faculty of Communications Science, Dr. Soetomo University, 2019)
Nowadays, any kind of information can easily be found on social media platforms, one of them is through the platform of Instagram. On Instagram we can find further information of the RICMA organization that has been chosen as the main topic of this research. RICMA is a non-profit muslim organization that is family based. This research aims to be a medium between people and also persuasion is done with the use of the Instagram account @ricmaupdate to invite youth followers of the account to become a member of the organization. Thus, the research method was conducted with the use of quantitative method using the CMC theory (Computer Mediated Communication). The participants of this research are the @ricmaupdate 96 active followers on Instagram, supported with the purposive sampling technique as well as questionnaires as the data collection method. This research shows there is an influence from the messages from @ricmaupdate’s Instagram account on the interest of young adults that are becoming Islamic Youth of Cut Meutia Mosque. Keywords: Message; Instagram; Interest; Muslim Teenagers; Cut Meutie Mosque